Human cadaver burial depth affects soil microbial and nutrient status - Pawlett, Mark; Rickson, Jane; Niziolomski, Joanna; Churchill, Sophie; Kešner, Michal (​Forensic Archaeology, Anthropology and Ecology, 2019)
Shallow burial (c. <0.3m) of human cadavers provides an alternative to standard burial depth (c. 1.0m) as this can enhance the natural recycling of nutrients to the soil through improved interactions between the corpse and the soil. However, there is a paucity of knowledge describing the interactions between the human cadaver and soil microbiology. The effects of shallow (pork) compared to standard burial depth (in a sandy loam and clay soil) identified that plant available nitrogen was consistently greater where the pork was shallow buried. There was also a shift in the soil’s bacterial community, but only in the sandy loam soil. Burial depth did not affect soil organic matter, available phosphorus, total microbial biomass or activity, or fungal biomass. The response of the bacterial community composition in the clay soils is likely due to reduced pore space and hence reduced oxygen at depth.